2020
DOI: 10.3389/fonc.2020.01602
|View full text |Cite|
|
Sign up to set email alerts
|

CDKL3 Targets ATG5 to Promote Carcinogenesis of Esophageal Squamous Cell Carcinoma

Abstract: Objective: Our previous study suggested cyclin-dependent kinase-like 3 (CDKL3) acts as a new oncogene in esophageal squamous cell carcinoma (ESCC) cell line TE-1. However, the molecular mechanisms and biological effects of CDKL3 in ESCC remain unknown. In the present study, we aimed to explore the clinical significance of CDKL3 in ESCC and how CDKL3 regulates the malignant behavior of ESCC. Methods: ESCC samples were stained by immunohistochemical staining (IHC) and analyzed for the expression of CDKL3. The fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The exclusion criteria were: (1) Non-ESCC patients; (2) Without a completed postoperative report of pathological assessment;(3) Without enough samples stored in the tissue bank of Taizhou Hospital. The flow of immunohistochemical staining (IHC) was carried out as we described in the previous study ( 22 ). Two observers blinded to the purpose of the study independently evaluated the stained sections.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The exclusion criteria were: (1) Non-ESCC patients; (2) Without a completed postoperative report of pathological assessment;(3) Without enough samples stored in the tissue bank of Taizhou Hospital. The flow of immunohistochemical staining (IHC) was carried out as we described in the previous study ( 22 ). Two observers blinded to the purpose of the study independently evaluated the stained sections.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study analyzed the profile of differential expressed genes between KYSE-150-NC and KYSE-150-CDKL3-KD cells using GeneChip ® PrimeViewTM human gene expression arrays ( 22 ). In this study, we used IPA to perform gene enrichment analysis based on the results of CDKL3 expression-related differential gene expression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across PC xenograft and mice models, autophagy inhibition via small hairpin RNA (shRNA) or small molecule inhibitors targeting ATG5 causes tumor regression and longer survival because ATG5 and ATG7 proteins are required for autophagosome formation [ 8 , 52 ], and ATG5 or ATG7 gene deletions reduce autophagy effects [ 53 ]. A mouse model with carcinogenic KRAS expression in pancreatic cells in the presence of two, one, or no Atg5 gene copies found that reduced Atg5 protein levels enhance tumor formation, but the absence of Atg5 prevents tumorigenesis [ 54 ]. Therefore, when primary PC cell lines lacking Atg5 were injected into a mouse, they observed improved intrusive and metastatic capability.…”
Section: Interactions For Both Autophagy and Pdacmentioning
confidence: 99%